Analisis Ayat-Ayat dalam Al-Qur’an Tentang Hukum Ibadah dan Muamalah - Sobarna, Nanang (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2026)
The Qur'an is a source of law in Islam in determining a law for a case. In the Al-Qur'an there is a classification of verses, namely verses regarding worship and muamalah. In the study of ushul fiqh, the Qur'an is the object of study of ushul fiqh in the sense of being a source of law. So that every discussion of the Koran in the science of Ushul Fiqh is intended to produce fiqh laws. Problems in the field of religious law and especially in the field of muamalah have emerged quite a lot in accordance with developments over time, making it interesting to discuss as an object of study on ushul fiqh. The verses or arguments regarding worship and muamalah themselves are references so that they can be used as references for mujtahids in determining laws regarding problems that arise. The aim of this research is to analyze the views of ushul fiqh in the verses of the Qur'an regarding the laws of worship and muamalah. So that the verses regarding the laws of worship and muamalah become references and considerations in every legal determination. The method used in this research uses a qualitative approach, with the type of library research. The results of the discussion in this research are that ushul fiqh is inherent in the establishment of laws that adhere to dilalah or lafazh expressions both in verses about the law of worship and muamalah. If the word is command or amr then the law becomes mandatory. The use of sadd adz-dzari'ah rules in the muamalah verse contains a form of caution, and the use of ijma in muamalah is solely to achieve the benefit of human life. Keywords: Law of Worship Verses, Muamalah Verses, Ushul Fiqh.